Spatial distribution of status silicon availability for plant and its effect to rice yield - Qurrohman, Budy Frasetya Taufik; Suriadikusumah, Abraham; Joy, Benny; Sudirja, Rija (Universitas Sebelas Maret, 2023)
Silicon (Si) is a beneficial element for rice plants. However, evaluating the Si availability status of paddy soil is rarely done. This study aimed to investigate the Si availability for plant (SiAP), spatial distribution, SiAP correlations with some soil properties and the effect of SiAP status on the rice yield. This study used a survey method to collect paddy soil and water sample. The pot experiment method was used to evaluate paddy plant response to SiAP level. Based on K-means, cluster analysis showed that soil SiAP was categorized low (< 147 mg SiO2 kg-1), moderate (147 – 224 mg SiO2 kg-1) and high (> 224 mg SiO2 kg-1). The SiAP status of the paddy soil area of 26,395 hectares (25%), 61,744 hectares (59%) and 15,952 hectares (15%) was categorized as low, moderate and high, respectively. This present study revealed that the upland area paddy soil has higher SiAP than the lowland area. Total silicon dioxide (SiO2) and clay percentage were negatively correlated with the SiAP in soils. Silicon addition to the paddy soil with SiAP status showed low to high increase in rice yield by 0.2%, 3.9% and 2.7%.